Magnetic and gravity views of crust and lithosphere heterogeneity in the Wilkes Subglacial Basin of East Antarctica - Egidio Armadillo; Fausto Ferraccioli; Alessandro Ghirotto; Duncan Young; Donald Blankenship; Martin Siegert (2020)
The Wilkes Subglacial Basin (WSB) is a major intraplate tectonic feature in East Antarctica. It stretches for ca 1400 km from the edge of the Southern Ocean, where it is up to 600 km wide towards South Pole, where it is less than 100 km wide. Recent modelling of its subice topography (Paxman et al., 2019, JGR) lends support to a long-standing hypothesis predicting that the wide basin is linked to exure of more rigid and mostly Precambrian cratonic lithosphere induced by the Cenozoic uplift of the adjacent Trasantarctic Mountains,. However, there is also mounting evidence from potential eld and radar exploration that its narrower structurally controlled sub-basins may have formed in response to more localised Mesozoic to Cenozoic extension and transtension that preferentially steered glacial erosion (Paxman et al., 2018, GRL). Here we exploit recent advancements in regional aerogeophysical data compilations and continental scale satellite gravity gradient imaging with the overarching aim of helping unveil the degree of 4D heterogeneity in the crust and lithosphere beneath the WSB. New views of crustal and lithosphere thickness stem from 3D satellite gravity modelling (Pappa et al., 2019, JGR) and these can be compared with predictions from previous exural modelling and seismological results. By stripping out the computed eects of crustal and lithosphere thickness variations we then obtain residual intra-crustal gravity anomalies. These are in turn compared with a suite of enhanced aeromagnetic anomaly images. We then calculate depth to magnetic and gravity source estimates and use these results to help constrain the rst combined 2D magnetic and gravity models for two selected regions within the WSB. One rst model reveals a major lithospheric scale boundary along the eastern margin of the northern WSB. It separates the Cambro-Ordovician Ross Orogen from a newly dened composite Precambrian Wilkes Terrane that forms the unexposed crustal basement buried beneath partially exposed early Cambrian metasediments and more ...